Isolation and Identification of Food Poisoning Bacteria from some Dairy Farms in El-Menoufia Governorate using VITEK 2 - Nada, Shaimaa M.; Elnahriry, Shaimaa S.; Sultan, Ahmed A.; Gaffer, Mohamed H. (Journal of Advanced Veterinary Research, 2023)
Because milk is rich in nutrients, it creates an environment conducive to the growth of bacteria that could be harmful to consumers. Therefore, assessing of its bacteriological quality and the resistance of these pathogens to several antibiotic groups is very important. VITEK 2 compact detected E. coli, Salmonellae spp., S. aureus and B. cereus in the examined samples while it failed to detect Listeria spp. The serological identification of E. coli showed the presence of O44: H18, O127: H6, O159, O15: H2, and O91: H21. Also, Salmonella serotypes as S. enteritidis (25%), S. infantis (12.5%), S. kentucky (12.5%), S. montevideo (6.25%), S. shangani (12.5%), S. tsevie (12.5%). S. typhimurium (18.75%). Furthermore, the entero-toxigenic strains of S. aureus were 31.25% of the identified strains; the percentage of entero-toxigenic strains that secrete A, A&C and D enterotoxin were 60%, 20% and (20%); respectively. Ampicillin, amoxicillin / clavulanic acid, cefpodoxime, cefovecin, ceftiofur, and trimethoprim / sulfamethoxazole were all ineffective against the isolated E. coli strains. Intermediate sensitive to cefalothin while they were sensitive to cefalexin, imipenem, amikacin, gentamicin, neomycin, enrofloxacin, marbofloxacin, pradofloxacin, doxycycycline, tetracycline, nitrofurantoin and chloramphenicol. Additionally, the isolated S. aureus exhibited resistance to tetracycline, benzylpenicillin, oxacillin, gentamycin, ciprofloxacin, levofloxacin, and moxifloxacin also; it showed intermediate resistance to rifampicin. The identified S. aureus strains were also susceptible to linezolid, nitrofurantoin, vancomycin, tigecycline, and trimethoprim / sulfamethoxazole.